2010
DOI: 10.1111/j.1467-6427.2010.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing the couple perspective in parenting support: evaluation of a service initiative for vulnerable families

Abstract: The importance of the relationship between parents is frequently underestimated by those designing and developing services to support parents in bringing up their children. Instead, the primary focus of recent family support initiatives in the United Kingdom has been on improving parenting skills. This article describes the outcomes of a project designed to maximize the effectiveness of parenting support to vulnerable families through sensitizing the workforce of a community‐based adult mental health agency to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This, in turn, was expected to enhance children's well-being and reduce dependence on welfare. Similar efforts have been contemplated in the United Kingdom (Clulow & Donaghy, 2010) and Australia (Halford & Simons, 2005), but the focus of initiatives in these two countries focused primarily on parenting programs rather than RE.…”
Section: Prevention and Public Policymentioning
confidence: 99%
“…This, in turn, was expected to enhance children's well-being and reduce dependence on welfare. Similar efforts have been contemplated in the United Kingdom (Clulow & Donaghy, 2010) and Australia (Halford & Simons, 2005), but the focus of initiatives in these two countries focused primarily on parenting programs rather than RE.…”
Section: Prevention and Public Policymentioning
confidence: 99%
“…Previous studies have reported that parenting efficacy is significantly correlated with a mother's self‐esteem (Tahmassian, Anari, & Fathabadi, ), parenting stress (Clulow & Donaghy, ; Tahmassian et al, ), parenting satisfaction (Coleman & Karraker, ), parenting behaviors (Thomas, Feeley, & Grier, ), children's behavioral problems (Tahmassian et al, ), social support (Ardelt & Eccles, ), and financial status (O'Neil, Wilson, Shaw, & Dishion, ). However, earlier studies conducted to explore individual relationships between parenting efficacy and related factors did not use a theoretical framework, or were not specifically focused on immigrant women.…”
Section: Introductionmentioning
confidence: 99%
“…For families on the cusp of having their children taken into government custody, parental support and training for parents has been associated with creating healthy families [15,42-44]. Given the association between parental substance use and youth exposure to the child welfare system, a focus on addiction treatment within parental support programs appears to be particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Together these study findings highlight that youth with a history of being in government care are significantly more susceptible to substance use and street-involvement later in life, suggesting that action is needed on multiple fronts. For families on the cusp of having their children taken into government custody, parental support and training for parents has been associated with creating healthy families [ 15 , 42 - 44 ]. Given the association between parental substance use and youth exposure to the child welfare system, a focus on addiction treatment within parental support programs appears to be particularly relevant.…”
Section: Discussionmentioning
confidence: 99%